VILLAGE COMMUNITY BASED JOURNALISTIC WORKSHOP - Zulkarnain Hamson; St. Shofiyah; Rostini Rostini; Arjang Arjang; Andi Azhar Aljurida (JCES (Journal of Character Education Society), 2021)
Abstrak: Jurnalistik desa dengan tujuan membangun kekuatan informasi desa dalam menunjang publikasi potensi dan aktifitas desa, saat ini menjadi prioritas yang tidak bisa dihindari, terlebih akuntabilitas manajemen pemerintahan desa, bisa sangat terbantu. Untuk itu, pola pengelolaannya didistribusikan kepada masyarakat, sehingga akan lebih meningkatkan peran serta masyarakat dalam membangun daerahnya. Pelibatan masyarakat desa, justru membuka ruang bagi kemunculan dan kepercayaan public pada kinerja aparat desa. Sisi lain yang diharapkan dari keterlibatan masyarakat adalah kedekatan mereka pada problematika desa, juga menjembatani public dan desa dimana mereka berdiam. Pelatihan ini dinilai berhasil menaikkan tingkat keprihatinan masyarakat pada problematika desa, dan menyuarakan berbagai potensi yang dimilikinya. Peserta workshop terdiri dari wakil ibu rumahtangga, perempuan, remaja dan tenaga motifator desa. Peserta dilatih secara teknis membuat berita desa, dengan pedoman penulisan berita komerial. Hasilnya 25 peserta mampu menuliskan informasi desa yang siap dipublikasi, baik media social maupun media komersial.Abstract:  Village journalism with the aim of building the strength of village information in supporting the publication of village potential and activities is currently an unavoidable priority, especially the accountability of village government management, which can be greatly helped. For this reason, the management pattern is distributed to the community, so that it will further increase community participation in developing their regions. Involving village communities, in fact opens space for the emergence and public confidence in the performance of village officials. Another aspect that is expected from community involvement is their closeness to village problems, as well as bridging the public and the village where they live. This training is considered successful in raising the level of community concern on village problems and voicing the various potentials it has. Workshop participants consisted of representatives of housewives, women, youth and village motivator staff. Participants are trained technically in making village news, with guidelines for writing commercial news. As a result, 25 participants were able to write village information that was ready to be published, both social media and commercial media.